Ta’lîm ‘Ilmi Fônôlôjiyâ (‘Ilmu Al-Ashwat) ladâ Thôlibât Qism Al-I’dad Al-Lughowî bi Jâmi’ah Ar-Raayah Sukabumi: تعليم علم فونولوجيا (علم الأصوات) لدى طالبات قسم الإعداد اللغوي بجامعة الراية سوكابومي - Mufarokah, Siti; Istiadah, Istiadah; Gazali, Zuhdina; Fuad, Nabilah Ahmad (Civilization Research: Journal of Islamic Studies, 2024)
This research was written to find out the profile of STIBA Ar-Raayah and examine phonology learning (imu ashwath) at STIBA Ar-Raayah Sukabumi, West Java. This research uses descriptive qualitative methods. The results of this research are that STIBA Ar-Raayah Sukabumi is one of the campuses in Indonesia that implements an active Arabic language program for its students. So phonology lessons (ashwath science) receive attention, because phonology (ashwath science) is a basic element in a language. The pattern of learning phonology (ashwath science) at STIBA Ar-Raayah is to use a curriculum that has been determined by STIBA Ar-Raayah. And the method used by the STIBA Ar-Raayah lecturer in this lesson is a reciprocal method between teacher and student, the teacher gives an example and the students follow. The book used in the phonology course (ashwath science) is the book Ashwath Al-'Arabiyah Li Ghoiri An-Nathiqina Biha written by Dr. Abdurrahman Bin Ibrahim Al-Fauzan. Evaluation of phonological science learning (ashwath science) at STIBA Ar-Raayah is carried out by giving assignments, quizzes, monthly exams and semester exams.